A REVIEW ON TEACHING WRITING BY APPLYING BLOGGERS APPLICATION - Shakilla Fasha; Zuhri Efendi (Journal Informatic, Education and Management (JIEM), 2026)
Writing is often considered a difficult skill to master, especially in language learning. One possible solution to this problem is the use of digital platforms such as Blogger. This study aims to analyze the strengths and weaknesses of using Blogger in teaching writing based on previous research. A systematic review of the literature that was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) process in several databases. the reviewed journals showed that that Blogger is an effective instructional medium for enhancing students’ writing skills, particularly in idea development, organization, coherence, and learning motivation. The platform supports a process-based writing approach by enabling drafting, revising, publishing, and interaction with an authentic audience, which fosters reflective and collaborative learning. Empirical evidence from Indonesian EFL consistently indicates notable improvements in students’ writing performance following blog-based instruction. Nevertheless, due to its limited impact on linguistic accuracy and its reliance on teacher scaffolding and students’ digital literacy, Blogger should be integrated as a complementary tool within a blended pedagogy that combines technology with explicit language instruction and systematic feedback.